The multiform character of public administration in crisis management - Ura, Elżbieta; Pieprzny, Stanisław (The Opole Studies in Administration and Law, 2019)
The paper presents the multiformity of public administration in crisis management from the subjective and material points of view. The provisions contained in the Act of 26 April 2007 on crisis management were analyzed. The act implies that the authorities of the general government and the local government at the level of the municipality and the district also are the crisis management authorities, and together with the subsidiary bodies create a specific system of public administration in this area. At the same time, it was pointed out that the statutory system of organs was incomplete, because in the crisis situations, specialist services (Police, State F ire Brigade, Army) and non-governmental organizations play a vital role. This multidimensionality allows distinguishing two groups of entities in crisis management: crisis management bodies and entities that perform tasks in crisis situations. In addition, the multiform nature of public administration in crisis management is evident in the presentation of this management in a material way: action preparation, civilian planning, risk prevention, fighting, reintegration.